A preliminary study on the effects of anaerobes on wastewater treatment using the granulated activated carbon upflow column - Lombos, Ruther Dennis S. (Animo Repository, 1995)
This study is about the comparison of the efficiency of Granulated Activated Carbon (GAC) up flow columns with and without anaerobes. The efficiency was evaluated by determining the COD and BOD reduction of the treated wastewater samples, using the GAC columns. Two retention times, 2 hours and 2 days, were also used to determine its effect in the reduction of BOD and COD levels. Overall, the result of the study showed that the anaerobes will lower the efficiency of the GAC up flow column. It also showed that the 2 days retention time without microorganisms will result in a clearer effluent and higher BOD and COD reduction.